1988
DOI: 10.1002/jcp.1041350304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat shock on RNA metabolism in HeLa cells

Abstract: Incubation of HeLa cells at 42 degrees C results in pronounced inhibition of the accumulation of 18S and 28S ribosomal RNA (rRNA) and non-heat shock polyadenylated messenger RNA (mRNA) in the cytoplasm. Accumulation of transfer RNA and 5S ribosomal RNA is not affected. Transcription of rRNA precursor is reduced to approximately 50% of the 37 degrees C rate after 10 min of hyperthermia and declines to 30% of the control rate after 1 hr. In contrast, the accumulation of mature rRNA in the cytoplasm is inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 55 publications
4
35
0
Order By: Relevance
“…This finding is consistent with results of the recent study by Sadis et al (42), who also examined heat shock in HeLa cells; they propose that the decreased accumulation is due to instability of the newly synthesized rRNAs. One possible explanation for the apparent discrepancy in the amounts of newly synthesized rRNA after heat shock in human cells may be related to the fact that both our study and that of Sadis et al (42) analyzed rRNAs shortly (1 to 4 h) after induction of the heat shock, whereas in the earlier study (47) the stress was inflicted upon the cells for at least 13 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 It has recently become clear that different stresses that induce HSPs can vary in their effects. For example, Bond found that heat shock and sodium arsenite treatment had differing effects on pre-mRNA splicing (8).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with results of the recent study by Sadis et al (42), who also examined heat shock in HeLa cells; they propose that the decreased accumulation is due to instability of the newly synthesized rRNAs. One possible explanation for the apparent discrepancy in the amounts of newly synthesized rRNA after heat shock in human cells may be related to the fact that both our study and that of Sadis et al (42) analyzed rRNAs shortly (1 to 4 h) after induction of the heat shock, whereas in the earlier study (47) the stress was inflicted upon the cells for at least 13 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 It has recently become clear that different stresses that induce HSPs can vary in their effects. For example, Bond found that heat shock and sodium arsenite treatment had differing effects on pre-mRNA splicing (8).…”
Section: Discussionsupporting
confidence: 93%
“…Release of nucleolin from the nucleolus can be mediated by a loss of its pre-rRNA binding substrate, which occurs in heated cells as heat exposure decreases rRNA synthesis (68,69). However, because nucleolin is a phosphoprotein that can be modified by several kinases including Cdc2, protein kinase C , and casein kinase II (56,57), and can also be methylated and ADP-ribosylated, it is possible that its translocation into the nucleoplasm is the result of post-translational modifications.…”
Section: Effects Of Heat On Nucleolin Localization In Vivo-mentioning
confidence: 99%
“…Heat shock is known to inhibit RNA transcription and mRNA processing (26,37), while low doses of ionizing radiation have relatively little affect. We investigated whether the slower rate of topoisomerase II␣ mRNA degradation in cells following irradiation could be accounted for by ongoing transcription.…”
Section: Vol 16 1996 Cell Cycle-regulated Expression Of Topoisomeramentioning
confidence: 99%